Efektivitas Media Bernyanyi Dalam Pembelajaran Mufradat Bahasa Arab Pada Anak Usia Dini - Nadia Putri Kusriani; Hikmah Maulani (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
Arabic is one of the international languages ​​that is important to learn and is also one of the foreign languages ​​that has been applied in the world of education. Of course, learning Arabic, which is foreign to Indonesians, is not easy. This is because Arabic has a lot of understanding. Therefore, it is necessary to have the right method to learn Arabic itself. This study aims to assess the effectiveness of the singing method in learning Arabic vocabulary in early childhood. This research uses a qualitative method with a descriptive approach with data collection techniques through observation and interviews. The results of the research show that the singing method is successful and effective for use in early childhood for learning Arabic vocabulary.